Representação da imagem pela velhice: a fotografia enquanto memória de indivíduos abrigados em instituto de longa permanência Asilo de Mendicidade de São Luís - CARVALHO, Francisca Rosemary Ferreira de (2012)
The old age which is housed in the Begging Asylum is taking photography as a methodological resource and instrument access to the memory of those individuals. We try to make reflections on the image to construct meanings, concept representation intrinsic to the sign seeking configure the photographic image as a representation of reality. Weaves a dialogue between photography and aging mechanisms as memory access and search the past. We present a study on aging in Western society through a brief history covering the ways in which the studies could advance reaching the status of science as well as advances in the aging process in post modernity. It highlights the positive and negative characteristics attributed to old age category that were built and that crystallized within sociocultural. Travels up the story of Begging Asylum of São Luís, with the founding period, according to the purpose of social panorama of the early twentieth century to get to today, with its new residents. Finally, we present images collected during interviews with inmates and assuming the role of search tool for memory. This interaction between age and allowed to photograph those visual images, which for some time were veiled in that environment.